Effects of Different Concentrations of Hemlock (Conium maculatum L.) Extracts on Myzus persicae (Sulzer) & Aphis fabae (Scopoli) (Hemiptera; Aphididae) - Mahmut İSLAMOĞLU; Vahdettin AKMEŞE (Türkiye Tarımsal Araştırmalar Dergisi, 2018)
Among the aphid species, Peachgreen aphid, Myzus persicae (Sulzer) and Blackbean aphid Aphis fabae (Scop) (Hemiptera: Aphididae) are two common pests causing significant damage in fruits, vegetables, and many other cultivated plants. Today, there is a great deal of chemical control against these harmful pests in our country and wide spectrum insecticides are used. Excessive chemicals are used in both pests because they have extreme reproductive ability and develop resistance to insecticides in a short time. For this reason, the negative effects of chemicals become permanent. Organic insecticides of plant origin in combating with aphids have been thought to replace chemical compounds and many studies have been carried out today with different plant extracts against different pests. In this study, the effects of different concentrations of the extract obtained from hemlock (Conium maculatum L.) plant on M. persicae and A. fabae were investigated. Three different concentrations of hemlock extract, 10%, 15% and 20%, were used to determine the biological effect on M. persicae and A. fabae using dipping and spraying methods. In the experiments, 50 adult individuals of M. persicae and A. fabae were used, live and dead individuals were counted at 1, 24, 48 and 72nd hours after the extract was applied. Experiments were established in 5 replications. According to the findings obtained, it was determined that the extract obtained from the hemlock plants had the highest biological effect at 20% extract concentration.